覆盆子의 내피세포의존성 혈관이완효과 - 진준호(Jun Ho Chin); 박선영(Sun Young Park) (동의생리병리학회지, 2013)
This study was investigated to evaluate the vasorelaxant effect of Rubus coreanus(RC) extract on contracted rabbit carotid artery and its mechanism. To study the effect of RC extract on contracted rabbit carotid arterial strips, arterial strips with intact or damaged endothelium were used for experiment using organ bath. The pre-contracted arterial strips with norepinephrine(NE) or potassium chloride(KCl) was treated with various concentrations of an extract of RC(0.01, 0.03, 0.1, 0.3 and 1.0 ㎎/㎖). To determine the mechanisms of RC-induced vasorelaxant, RC extract was infused into contracted arterial rings which had been pretreated by indomethacin(IM), tetraethylammonium chloride(TEA), Nω-nitro-L-arginine (L-NNA), methylene blue(MB). And calcium chloride(Ca) 1 mM was infused into precontracted arterial ring induced by NE or KCl after treatment of RC extract in Ca2+-free krebs solution. Cytotoxic activity of RC extract on human umbilical vein endothelial cell(HUVEC) was measured by MTT assay, and nitric oxide(NO) prodution was measured by Griess reagent. RC extract revealed significant relaxation on NE-induced arterial contraction, but didn't relax on KCl-induced arterial contraction. RC extract also had an effective relaxation to the intact endothelium arterial ring, but not the damaged endothelium arterial ring. Treatment of IM, TEA, L-NNA, MB reduced the relaxation of RC extract. Pretreatment of RC extract inhibited the contraction by influx of extracellular Ca2+ in contracted arterial ring induced by NE, but it didn't work the contraction by influx of extracellular Ca2+ in contracted arterial ring induced by KCl in Ca2+-free krebs solution. RC extract increased nitric oxide production on HUVEC. This study indicated that the relaxation effect of RC extract on contracted rabbit carotid artery is related with NO-cGMP pathway, EDHF, prostacyclin. KCI Citation Count: 1